Adults with learning disabilities experiences of using community dental services: Service user and carer perspectives. (20th January 2017) - Lees, Carolyn; Poole, Helen; Brennan, Michelle; Irvine, Fiona
Abstract : Accessible summary: The government and other organisations say that improving health care is important for people with learning disabilities. We asked people with learning disabilities and the people who look after them what it was like for them when they went to the dentist. Those we asked said that when they went to the dentist, they knew that those they saw knew about looking after their teeth. Some of those we talked to though said that certain things needed to be better. Abstract: Background: The government alongside other health and social care organisation have identified the need to improve the care provided for people with learning disabilities. Materials and Methods: This service evaluation aimed to explore the experiences of people with learning disabilities and their carers who accessed community dental services using a qualitative research design. Adults with learning disabilities ( n = 4) and their carers ( n = 6) took part in one to one, face to face semi structured interviews. Results and Discussion: Generally, participants were satisfied with community dental services and in particular valued the skills and the competence of practitioners. However, when dissatisfaction was expressed this was generally as a result of poor communication and the transition from child to adult dental services. Conclusions: A number of recommendations are identified and discussed in relation to engagement with adults with learning disabilities and their carers in the development and delivery of community dental services.